(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Gridhrasi, a Nanathmaja vata vyadi, manifests in two distinct forms: Vataja and Vata-Kaphaja. Despite the availability of conventional treatments, patients often experience only temporary relief. Rasayana Chikitsa, a traditional approach, offers a promising long-term solution. This study aims to evaluate the effectiveness of Rasayana Chikitsa in managing symptoms of Gridhrasi and improving patient outcomes. Objectives: To evaluate the therapeutic effect of Vardhamana Balamoola Rasayana in Gridhrasi. Methodology: A randomized controlled clinical study was conducted on 30 patients, aged 18-70 years, who attended the outpatient department (OPD) of the institute with low back pain radiating to lower limbs. These patients met the diagnostic criteria and participated in the study. The participants were divided into two groups: Group A, which received Vardhamana Lashuna Rasayana for 16 days, and Group B, which received Vardhamana Balamoola Rasayana for 30 days. The treatment protocol involved mild purgation followed by incrementally increasing doses. Efficacy was assessed using both subjective criteria (pain, stiffness, functional ability) and objective criteria (Straight Leg Raise (SLR) test) at baseline, during treatment, and post-treatment. Statistical analysis was performed using paired t-tests, Wilcoxon’s signed-rank tests, unpaired t-tests, and Mann-Whitney U tests to evaluate the treatment outcomes. Results: Vardhamana Balamoola Rasayana showed superior efficacy, with 20% achieving maximum relief. It also had higher mild relief rates (46.66% vs. 26.66%) and lesser minimum relief rates (0% vs. 40%). Conclusion: Vardhamana Balamoola Rasayana demonstrated superior efficacy in pain management, functional ability, and neurological deficit reduction, making it a more effective therapeutic option for Gridhrasi symptom relief.